Signaling sizeism: An assessment of body size‐based threat and safety cues. Issue 1 (15th January 2022) - Oswald, Flora; Stevens, Samantha M.; Kruk, Mary; Murphy, Catherine I.; Matsick, Jes L.
Abstract: Pervasive stigma against fat people and evidence for its harmful health consequences highlight the need for a better understanding of people's first‐hand experiences of navigating the world with a stigmatized body size. Drawing on social identity threat theory, we conducted a mixed‐method study with a qualitative examination of threat and safety cues as experienced by people who self‐identify as overweight. In an online survey, 48 people who self‐identified as overweight responded to open‐ended prompts to describe how situational features of a setting signal weight‐based threat and safety to them. Using thematic analysis, we identified several themes that characterized threat and safety cues. Particularly notable were inverse themes, such as structural exclusion versus structural accommodation and homogeneity of others versus general diversity, that highlighted how physical features of, and the people in, an environment positively or negatively impact fat people's psychological experience. Moreover, we conducted exploratory deductive coding using a recent taxonomy of safety cues developed by Kruk and Matsick (in press). Results highlighted how weight‐based stigma both parallels and diverges from other cues of identity safety (e.g., by gender or race/ethnicity). We suggest knowledge about situational cues can inform interventions to mitigate threat and promote safety among both fat people and other stigmatized groups.